Study of clinical features and laboratory investigations for effective management of hyponatremia - Bhutto, M. G.; B. R., Sandeep; Shah, Sharath Kumar D.; ., Shabaz (International Journal of Research in Medical Sciences, 2020)
Background: Hyponatremia, a common electrolyte disorder is mostly observed in hospitalized elderly patients. It is a potential cause of morbidity, mortality and has significant economic impact on the patient and health care system. The aim of the present study was to investigate the risk factors, clinical features and management of hyponatremia in hospitalized patients to reduce its incidence and minimize the associated complications. Methods: Current study was conducted in a tertiary care hospital SSMC, Tumkur). Patients were evaluated for the underlying cause of hyponatremia through detailed history and physical examination followed by appropriate laboratory investigations based on urine sodium, serum and urine osmolality. Patients with hyponatremia were classified into categories based on clinical investigations and accordingly treated with suitable therapy. Results: Constitutional symptoms, confusion, fever, vomiting, respiratory symptoms, abdominal pain, loose stools, coma, convulsions and other miscellaneous symptoms were observed in history of hyponatremic patients. Most common etiology was found to be SIADH followed by extrarenal losses, renal failure, cirrhosis, CCF, drug in take and glucocorticoid deficiency. Management of hyponatremia was done using hypertonic saline, administration of diuretics, fluid restriction therapy, administration of vaptans and combination of hypertonic saline and vaptans as treatment alternatives, no potential complications were observed during treatment of hyponatremia. Conclusions: The possible cause of hyponatremia should always be determined, asoutcomeinsevere hyponatremiais governed by etiology and not merely by serum sodium levels. The correction of hyponatremia helps to improve the prognosis of the underlying disease and to prevent further complications.